1995
DOI: 10.1161/01.str.26.11.2135
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical Neural Sprouting, Synaptogenesis, and Behavioral Recovery After Neocortical Infarction in Rats

Abstract: These data support the occurrence of neurite growth followed by synaptogenesis in the neocortex, ipsilateral and contralateral to neocortical ischemia, in a pattern that corresponds both spatially and temporally with behavioral recovery. Thus, neuroanatomical remodeling in the neocortex provides a mechanism for recovery of function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
285
2
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(300 citation statements)
references
References 47 publications
10
285
2
3
Order By: Relevance
“…Diffusion remote from MCA infarctsform synapses in previously empty spaces (Carmichael, 2003;Kristt, 1987;Stroemer et al, 1995Stroemer et al, , 1998). An alternative explanation would be a transient increase in axonal density related to neuronal regeneration as observed in the ipsilateral striatum and hippocampus in animal models of MCA occlusion (Nadareishvili and Hallenbeck, 2003;Nakatomi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion remote from MCA infarctsform synapses in previously empty spaces (Carmichael, 2003;Kristt, 1987;Stroemer et al, 1995Stroemer et al, , 1998). An alternative explanation would be a transient increase in axonal density related to neuronal regeneration as observed in the ipsilateral striatum and hippocampus in animal models of MCA occlusion (Nadareishvili and Hallenbeck, 2003;Nakatomi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This cortical reorganization may be mediated by two mechanisms. Firstly, the activation of previously latent neural networks in residual tissue may take on the function of the lost tissue (Sigler et al, 2009); alternatively, enhanced axonal sprouting, synaptogenesis, and dendritic spine turnover (Biernaskie and Corbett, 2001;Brown et al, 2007Gonzalez and Kolb, 2003;Stroemer et al, 1995;Winship and Murphy, 2009) may support reorganization of residual tissue such that it can support the function of the lost tissue. Again, the application of plasticity promoting factors such as environmental enrichment (Williams et al, 2006), behavioural therapy (Adkins et al, 2006;Kleim et al, 2004), pharmacological treatments (MacDonald et al, 2007), and neurotrophic factor application (Monfils et al, 2005) have been shown to facilitate reorganization of cortical maps.…”
Section: Electrophysiological Changesmentioning
confidence: 99%
“…On the other side, there is evidence of a range of responses to tissue injury to produce a facilitatory environment for repair, including upregulation of growth factor genes and promoters of angiogenesis, enhanced plasticity, as well as mobilisation of endogenous neural stem cells. [12][13][14] The tissue outcome of stroke ultimately, however, is a cystic fluid-filled space of variable volume, surrounded by a gliotic rim.…”
Section: Introductionmentioning
confidence: 99%